A literature review of flexible development of airport terminals. Issue 3 (4th May 2017) - Magalhães, Liliana; Reis, Vasco; Macário, Rosário
ABSTRACT: The Master Plan has long been the traditional go-to approach to airport development. It was originally conceived for a scenario of stable growth. In recent decades, however, the airport industry has undergone substantial structural changes, with the traditional Master Plan progressively revealing limitations with regard to airports coping with the market's unpredictability. There have since been increased calls for flexibility in the approach as an alternative or as a complement to the traditional Master Plan. A flexible development plan helps to accommodate changes within terminals. This paper presents a review of the current literature on airport terminal flexibility, covering a total of 19 reference works. The works were analysed in terms of the concepts, definitions and deployment frameworks, or similar. The review reveals that research in airport terminal flexibility is still in its early stages. A consensual definition has yet to be defined and no robust framework for deploying flexibility has been defined. We propose a new definition of flexible development. Furthermore, flexibility has been studied essentially in the context of expansion. However, in certain regions where land availability is scarce, other forms of airport development may be more important. We conclude the paper with suggestions for future research areas.